Współpraca polskiej i węgierskiej opozycji w latach osiemdziesiątych XX wieku - Kopyś, Tadeusz (Pamięć i Sprawiedliwość, 2010)
Poland and Hungary were experiencing very similar political transformations within their long history. Mostly, those changes were caused by a great similarity in the social and political structures between the two countries, but also by the simple fact of continued existence of the communist system in both societies. On the other hand, Poland and Hungary differed significantly on the issue concerning the specific Church’s position in Hungary and in Poland and on the role of masses in social movements. Peoples’ flexible attitude toward changing political situation in Hungary was revealed firstly, during the Hungarian Revolution of 1956 when the Imre Nagy’s government received an endorsement of the overwhelming majority of Hungarians. Then, after few years, people became drained of powerful emotions which led them – especially working class’ members – to the political inactivity. At the same time, in Poland, the opposition started playing crucial role in a way that, in the 1980s, resulted in establishing a framework of the civil society.This text deals with some major aspects of unique relation that existed between Poland and Hungary, especially from the mid-1970s till 1980s. For instance, the development of the opposition’s activity in both countries was dependent of each other’s influence. In consequence, it enabled them to build strong relationship thanks to which it became possible to commemorate the next anniversary of the 1956 Revolution (it happened for the first time on the east side of the Iron Curtain, before 1989). That relationship also provided a firm foundation for mutual assistance such as: Polish support for the development of Hungarianunderground literature or formal visits in Poland of particular Hungarian activists (Gábor Demszky).The Hungarian authorities channeled their efforts into stopping the wave of Polish transformations from occurring in Hungary, therefore any attempts of making direct contact were impeded and limited. What is more, the Hungarian agents of the security apparatus were being sent in Poland in order to scrutinize the nature of Polish political transformations.This article is rich in opinions of the Hungarian society concerning the revolutionary changes in Poland, as well as in their reactions to the formation of trade unions in the PRL (the Polish People’s Republic). The Author makes an attempt to find out why Hungarian workers’ mass did not follow suit the Polish ones which might seem to have been a logical consequence of better economic situation in Hungary.